Stem tilting in the inter‐tropical cactus Echinocactus platyacanthus: an adaptive solution to the trade‐off between radiation acquisition and temperature control. (29th August 2013) - Herce, M. F.; Martorell, C.; Alonso‐Fernandez, C.; Boullosa, L. F. V. V.; Meave, J. A.; Arroyo, J.
Abstract While plants require radiation for photosynthesis, radiation in warm deserts can have detrimental effects from high temperatures. This dilemma may be solved through plant morphological attributes. In cold deserts, stem tilting keeps reproductive organs warm by increasing radiation interception at the cost of decreased annual light interception. Conversely, little is known about stem tilting in warm deserts. We hypothesised that stem tilting in Echinocactus platyacanthus prevents high temperatures near the apex, where reproduction occurs. The study was conducted in the warm, inter‐tropical portion of the Chihuahuan Desert, Mexico. We found that cacti preferentially tilted towards the south, which reduced temperatures of reproductive organs during the hot season, but increased total annual near‐apex PAR interception. Tilting also maximised reproduction, a likely consequence of temperature control but perhaps also of the difficulty in translocating photosynthates in cacti; therefore, annual energy acquisition near floral meristems may be largely allocated to reproduction. Unlike plants of higher latitudes, in inter‐tropical deserts sunlight at noon comes either from the north or the south, depending on the season, and thus stem tilting may more strongly affect total annual radiation received in different portions of the stem. Inter‐tropical cacti can synchronise reproduction with irradiance peaks if flowering occurs in a specific (north or south) portion of the stem; also, they effectively solve the conflict between maximising annual PAR interception and minimising temperature at the hottest time of day. Notably, the two inter‐tropical cacti in which stem tilting has been studied successfully solve this conflict.